A cumulative genetic risk score predicts progression in Parkinson's disease. Issue 4 (8th February 2016) - Pihlstrøm, Lasse; Morset, Kristina Rebekka; Grimstad, Espen; Vitelli, Valeria; Toft, Mathias
Abstract: Background: The contribution of genetic variability to clinical heterogeneity in Parkinson's disease is insufficiently understood. We aimed to investigate the effect of cumulative genetic risk on clinical outcomes. Methods: In a single‐center study of 336 patients we genotyped 19 independent susceptibility variants identified in genome‐wide association studies of Parkinson's disease. We tested for association between a cumulative genetic risk score and 3 outcome measures: survival, time until progression to Hoehn and Yahr stage 3, and Unified Parkinson's Disease Rating Scale motor score severity. Results: Genetic risk score was significantly associated with time from diagnosis to Hoehn and Yahr stage 3 in a Cox regression model ( P = 0.010). We observed no clear association for the other outcomes. Conclusions: We present results linking cumulative genetic risk to a motor outcome in Parkinson's disease. Our findings provide a valuable starting point for future large‐scale efforts to map the genetic determinants of phenotypic variability. © 2016 International Parkinson and Movement Disorder Society